Peran Tokoh Masyarakat dalam Melestarikan Budaya Attabe': Perspektif Pendidikan Agama Islam - Muh. Nur Fithri D (STAI YAPIS Takalar, 2021)
This study examines the Role of Community Leaders in Preserving Attabe' Culture in Kalukubodo Village, South Galesong District, Takalar Regency. This study aims: (1) To find out the Attabe culture in the community leaders of Kalukubodo Village. (2) To find out the Role of Community Leaders in Preserving Attabe' Culture in Kalukubodo Village, South Galesong District, Takalar Regency. This research is a qualitative research that uses field research (Field Research) by conducting direct research on the object to be studied. The data collection techniques used are observation, interviews, and documentation. The source of this research data is directly to the resource person, namely Kalukubodo Village.After doing research, it is known that Attabe' culture is Bugis Makassar culture which has been handed down from ancestors and is still preserved by the community, especially the village of Kulukubodo, where we know Attabe' culture is a lesson or teaching about how to behave well, speak good words. and behave politely through one's actions or words to others. Attabe' culture is taught from childhood to adulthood so that the culture does not just disappear.The role of community leaders is very influential in preserving Attabe culture. By setting a good example and educating children from childhood until they grow up, they will be able to educate and teach children to behave well and will respect each other and have more respect for those who are older than them. In the village community of Kalukubodo, South Galesong sub-district, Takalar district still preserves the cultures or customs which they still consider to have a good influence in everyday life, including Attabe' culture itself.